2011
DOI: 10.1051/0004-6361/201016311
|View full text |Cite
|
Sign up to set email alerts
|

A Sino-Germanλ6 cm polarization survey of the Galactic plane

Abstract: Context.Observations of large supernova remnants (SNRs) at high frequencies are rare, but provide valuable information about their physical properties. Aims. The total intensity and polarization properties of 16 large SNRs in the Galactic plane are investigated based on observations of the Urumqi λ6 cm polarization survey of the Galactic plane with an angular resolution of 9. 5. Methods. We extracted total intensity and linear polarization maps of large SNRs from the Urumqi λ6 cm survey, obtained their integra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
98
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 82 publications
(108 citation statements)
references
References 97 publications
9
98
0
1
Order By: Relevance
“…The spectral index of the SNR G206.9+2.3 presents fairly uniform distribution and has an averaged index of β = −2.46, similar to the value found for its integrated flux densities by Gao et al (2011). Spectral index values are generally about −0.4 in the Monoceros SNR shell region.…”
Section: Spectral Index Mapsupporting
confidence: 49%
See 1 more Smart Citation
“…The spectral index of the SNR G206.9+2.3 presents fairly uniform distribution and has an averaged index of β = −2.46, similar to the value found for its integrated flux densities by Gao et al (2011). Spectral index values are generally about −0.4 in the Monoceros SNR shell region.…”
Section: Spectral Index Mapsupporting
confidence: 49%
“…35+1.35) in the eastern periphery from its thermal spectrum. Gao et al (2011) showed a new polarization observation at 4800 MHz. Combining this observation with Effelsberg 21 cm and 11 cm data, they obtained a spectral index of α = −0.43 ± 0.12 for the western shell.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we present new λ6 cm and λ11 cm observations of CTA 1, which is one of the targets of a campaign to map large northern sky SNRs at λ6 cm. This project is part of the Sino-German λ6 cm polarisation survey of the Galactic plane Gao et al 2010;Sun et al 2011;Xiao et al 2011;Gao et al 2011). Results on some large SNRs have been already reported, such as G65.2+5.7 (Xiao et al 2009), the Cygnus Loop (Sun et al 2006), HB 3 (Shi et al 2008), G156.2+5.7 (Xu et al 2007), and S 147 (Xiao et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Many SNRs have been detected as strong discrete sources in the survey. A study of large SNRs with angular sizes exceeding about 1 • was presented by Gao et al (2011). In this paper, we focus on SNRs with a smaller angular size.…”
Section: Introductionmentioning
confidence: 99%